2022
DOI: 10.3390/ma15217412
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Autogenous Shrinkage of Concrete Incorporating Super Absorbent Polymer and Waste Materials through Individual and Ensemble Machine Learning Approaches

Abstract: The use of superabsorbent polymers, sometimes known as SAP, is a tremendously efficacious method for reducing the amount of autogenous shrinkage (AS) that occurs in high-performance concrete. This study utilizes support vector regression (SVR) as a standalone machine-learning algorithm (MLA) which is then ensemble with boosting and bagging approaches to reduce the bias and overfitting issues. In addition, these ensemble methods are optimized with twenty sub-models with varying the nth estimators to achieve a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 149 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…The findings of the research have demonstrated that the aggregate that is obtained from waste glass can, in fact, be utilized fruitfully in the manufacturing of polymer concrete [ 21 , 22 ]. The application of super absorbent polymers (SAP), also referred to simply as SAP, is a technique that has proven to be extraordinarily effective in reducing the amount of autogenous shrinkage (AS) that takes place in high-performance concrete [ 23 , 24 ]. This technique is also sometimes referred to as SAP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the research have demonstrated that the aggregate that is obtained from waste glass can, in fact, be utilized fruitfully in the manufacturing of polymer concrete [ 21 , 22 ]. The application of super absorbent polymers (SAP), also referred to simply as SAP, is a technique that has proven to be extraordinarily effective in reducing the amount of autogenous shrinkage (AS) that takes place in high-performance concrete [ 23 , 24 ]. This technique is also sometimes referred to as SAP.…”
Section: Introductionmentioning
confidence: 99%
“…The concrete’s shrinkage can be efficiently improved by combining a SAP with preabsorbed water, and this combination produces a shrinkage reduction impact that is more pronounced than the effect produced by simply adding the SAP dry. Concrete can be efficiently prevented from cracking if a SAP is added to it [ 23 , 24 , 25 , 26 ]. This will enhance the microstructure of the concrete, which will improve its density as well as its resistance to cracking.…”
Section: Introductionmentioning
confidence: 99%